Scientific Analysis of Linguistic Branches: Identifying Linguistic Fields in Indonesian Elementary Textbooks the Merdeka Curriculum - Nurul Hidayah, Safitri; Viola, Albita Intan; Ikrimah, Fani; Hidayati S., Nur (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines four fundamental components of linguistics—morphology, syntax, semantics, and pragmatics—as the essential foundation for developing students’ language competence at the elementary school level. The research focuses on an in-depth analysis of how word structure, sentence structure, meaning systems, and contextual language use interact to form comprehensive linguistic ability. The morphological discussion highlights word-formation processes, including affixation, reduplication, and compounding, as well as the role of morphemes as the smallest meaningful units. The syntactic analysis explores the organization of phrases, clauses, and sentence types to understand how utterances are grammatically constructed. Furthermore, the semantic section emphasizes lexical, denotative, and grammatical meanings as the basis for accurate interpretation of words and sentences. The pragmatic analysis addresses the importance of context in determining the intended meaning and function of utterances, and how language use is shaped by communicative situations. The findings indicate that these four linguistic aspects are inherently interconnected, functioning collectively within the language-learning process. Morphology provides the fundamental building blocks of words, syntax organizes these elements into coherent structures, semantics offers interpretative frameworks, and pragmatics ensures that language is used appropriately within various contexts. This study concludes that language instruction at the elementary level should be designed comprehensively by integrating all linguistic components. Such a holistic approach is believed to significantly enhance students’ literacy skills and communicative competence, both in academic settings and in everyday interactions.